CONQUIRO: A cluster-based meta-search engine. - Vargas-Vera, Maria; Castellanos, Yesica; Lytras, Miltiadis D. (Computers in Human Behavior, 2011)
This paper presents CONQUIRO a cluster based information retrieval engine. The main task of CONQUIRO is to organize documents in groups/clusters relevant to the request or query. The main purpose of CONQUIRO is to help to manage information in an efficient manner. CONQUIRO uses Machine learning algorithms (Clustering methods) as underlying technology. It has been equipped with hierarchical and non-hierarchical clustering algorithms both using Euclidean and cosine similarity as distance measures. Authors believe that CONQUIRO represents a solution to the problem of information management since CONQUIRO goes beyond just a ranked list of documents (Google like).